THE USE OF VERTEBRATE EDUCATIONAL TEHNALOGIES IN THE TEACHING OF TOPICS RELATED TO MICROORGANISMS IN BIOLOGY LESSONS - S.R.Otajonova; Isaqjonova Nihola Qurbonboy qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Subject of microorganisms, the use of vertual talim tehnalogies in the study is the most effective mitigation process.Because in the process of roasting, experiments that do not have time are treated.Vertical experiments are done for example to experiment with viruses no honadaimkoni therefore, the use of virtual education in the present-day training is the most effective educational method.It also provides virtual training remote control.in the event that the bundaocutter falls ill, verual hands over.does not get left of classes.